2001
DOI: 10.1002/cb.56
|View full text |Cite
|
Sign up to set email alerts
|

Practice paper 21st‐century consumer society

Abstract: Co-founder, The Future Foundation. The Future Foundation is a future-oriented commercial think-tank which advises companies on better ways to market to, and communicate with, their customer base. The Future Foundation research into changing social values and consumer behaviour began in 1996 with Changing Lives, proprietary research into emerging values. It continued in 1997 with The 24-Hour Society, a review of the extending hours of consumer culture, undertaken on behalf of First Direct and BT. This was follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2011
2011

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…The ongoing value shift from a collectivist view to a more individualist view of everyday life emphasizes self‐expression and quality of life (Firat and Schultz, 1997). Research has shown that generations born in the 1970s, 1980s, and 1990s have questioned modern values and replaced them with post‐modern values in everyday and working life (Inglehart, 1997; Howard and Mason, 2001).…”
Section: Theoretical Assumptionsmentioning
confidence: 99%
“…The ongoing value shift from a collectivist view to a more individualist view of everyday life emphasizes self‐expression and quality of life (Firat and Schultz, 1997). Research has shown that generations born in the 1970s, 1980s, and 1990s have questioned modern values and replaced them with post‐modern values in everyday and working life (Inglehart, 1997; Howard and Mason, 2001).…”
Section: Theoretical Assumptionsmentioning
confidence: 99%
“…The term "experience-oriented consumption" refers to consumption as a source of entertainment and enjoyment (Barbin et al, 1994). According to Howard and Mason (2001), a large proportion of customers attach great significance to the experience and excitement of consumption. In this regard, Hirschman and Holbrook (1982) noted that certain "hedonic goods" (such as sports cars or luxury watches) satisfy the desire of such customers for experiential enjoyment.…”
Section: Experience Orientationmentioning
confidence: 99%
“…Marketing on the internet is a relatively new but a fast-expanding strategy (Souitaris and Cohen, 2003;Howard and Mason, 2001). Since the appearance of banner advertising in 1994, consumers have been increasingly targeted with various sophisticated internet-based marketing techniques (Lohtia et al, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%